UJI EFEKTIVITAS MINYAK ATSIRI SERAI WANGI (Cymbopogon nardus L.) DALAM MENGENDALIKAN JAMUR (Alternaria porri) PENYEBAB PENYAKIT BERCAK UNGU PADA TANAMAN BAWANG PREI (Allium Fistulosum L.) - Abifah, Serlia Nur; Prasetyawati, Endang Triwahyu; Suryaminarsih, Penta (JURNAL AGROTROPIKA, 2025)
The growth and production of oil palm is greatly influenced by the presence of Plant Pest Organisms (OPT), one of which is purple spot disease caused by the fungus Alternia porri. Control efforts using vegetable fungicides, namely citronella essential oil. The aim of this research is to determine the concentration of citronella essential oil as a vegetable fungicide that is effective in suppressing the growth of the Alternaria porri fungus in vitro. This research was carried out from October-December 2023. The location of this research was carried out at the Plant Health Laboratory, Faculty of Agriculture, National Development University "Veteran" East Java. The research design used was a Completely Randomized Design (CRD) using a single factor of citronella essential oil concentration, namely 0%, 10%, 20%, 30% and 40%. Observation variables include the inhibition test. The data from the research was carried out using Analysis of Varience (ANOVA) and continued with a multiple comparison test using the BNJ advanced test at a real level of 5% using SPPS software version 21. The results of the research showed that the largest percentage of inhibitory power on the last day of observation was obtained at a concentration of 40%, namely amounting to 32.92% and 30% concentration, namely 20.29%, while the lowest inhibitory power was obtained from the 20% concentration treatment, namely 7.74% and 10% concentration, namely 8.89%. The higher the concentration of citronella essential oil used, the stronger the inhibition of fungal growth will be.Keywords : essential oils, citronella, concentrate, Alternia porri